The right place in the right space? Awareness of site for needle thoracocentesis. Issue 11 (21st October 2005) - Ferrie, E P; Collum, N; McGovern, S
Abstract : Background: Invasive practical procedures require identification of surface anatomical landmarks to reduce risk of damage to other structures. Needle thoracocentesis has specific complications, which have been previously documented. An observational study was performed among emergency physicians to name the landmark for needle thoracocentesis and identify this point on a human volunteer as per Advanced Trauma and Life Support (ATLS) guidelines. Results: A cohort of 25 emergency physicians was studied, 21 (84%) of which were ATLS certified. The correct landmark was named by 22 (88%). Only 15 (60%) correctly identified the second intercostal space on the human volunteer, all placing the needle medial to the midclavicular line, with a range of 3 cm. Two (8%) named and identified the site of needle pericardiocentesis; one (4%) named and identified the fifth intercostal space in the anterior axillary line. Discussion: These results demonstrate a low accuracy among emergency physicians in identifying correct landmarks for needle thoracocentesis under elective conditions. Should greater emphasis be placed on competency based training in ATLS?